Characterization of milk protein concentrate powders using powder rheometer and front-face fluorescence spectroscopy - Sajith Babu, Karthik (Kansas State University, 2018)
Milk protein concentrate (MPC) powders are high-protein dairy ingredients obtained from membrane filtration processes and subsequent spray drying. MPC powders have extensive applications due to their nutritional, functional, and sensory properties. However, their flow properties, rehydration behavior, and morphological characteristics are affected by various factors such as processing, storage, particle size, and composition of the powder. Literature has shown that knowledge about the powder flowability characteristics is critical in their handling, processing, and subsequent storage. For this study, FT4 powder rheometer (FT4, Freeman Technologies, UK) was used to characterize the flowability of MPC powders during storage. This study investigated the flowability and morphological characteristics of commercial MPC powders with three different protein contents (70, 80, and 90%, w/w) after storage at 25°C and 40°C for 12 weeks. Powder flow properties (basic flowability energy (BFE), flow rate index (FRI), permeability, etc.) and shear properties (cohesion, flow function, etc.) were evaluated. After 12 weeks of storage at 40°C, the BFE and FRI values significantly increased (P < 0.05) as the protein content increased from 70 to 90% (w/w). Dynamic flow tests indicated that MPC powders with high protein contents displayed higher permeability. Shear tests confirmed that samples stored at 40°C were relatively less flowable than samples stored at 25°C. Also, the lower protein content samples showed better shear flow behavior. The results indicated that MPC powders stored at 40°C had more cohesiveness and poor flow characteristics than MPC powders stored at 25°C. The circle equivalent diameter, circularity, and elongation of MPC powders increased as protein content and storage temperature increased, while the convexity decreased as protein content and storage temperature increased. Overall, the MPC powders evidently showed different flow properties and morphological characteristics due to their difference in composition and storage temperature. Literature has shown various methods for determining the solubility of dairy powders, but it requires expensive instruments and skilled technicians. The front-face fluorescence spectroscopy (FFFS) coupled with chemometrics could be used as an efficient alternative, which is commonly used as fingerprints of the various food products. To evaluate FFFS as a useful tool for the non-destructive measurement of solubility in the MPC powders, commercially procured MPC powders were stored at two temperatures (25 and 40°C) for 1, 2, 4, 8, and 12 weeks to produce powders with different rehydration properties, which subsequently influenced their fluorescence spectra. The spectra of tryptophan and Maillard products were recorded and analyzed with principal components analysis. The solubility index and the relative dissolution index (RDI) obtained from focused beam reflectance measurement was used to predict solubility and dissolution changes using fluorescence spectra of tryptophan and Maillard products. The solubility index and RDI showed that the MPC powders had decreased solubility as the storage time and temperature increased. The results suggest that FFFS has the potential to provide rapid, nondestructive, and accurate measurements of rehydration behavior in MPC powders. Overall, the results indicated that solubility and dissolution behavior of MPC powders were related to protein content and storage conditions that could be measured using FFFS.
Keywords: Milk Protein Concentrate Powders; Flowability; Solubility; Particle morphology; FT4 powder rheometer; Front-face fluorescence spectroscopy